Synthesis and Characterization of Versatile Polymer Particles for the Adsorption of Bromophenol Blue and Phenol - Kutalmış Gökkuş; Çiğdem Öter; Merilyn Amlani; Mahmut Gür; Vural Bütün (Research Square Platform LLC, 2023)
Abstract Removing anionic pollutants from water sources remains a major challenge in supramolecular chemistry. Today, cellulose, activated carbon, zeolite, and similar materials, which are widely preferred, have a weak effect against anionic pollutants. Therefore, further modifications are needed for the use of such substances. On the contrary, in this study, highly functional and economical polymeric particles (called GD particles) were synthesized with high yield and did not require further modifications. GD particles were synthesized with glutaraldehyde and diethylenetriamine as monomers for the first time. The structural properties of the synthesized particles were characterized by FT-IR, TGA, and SEM analyses. Then, GD particles were used in the adsorption of anionic Bromophenol blue and phenol. The isotherm, thermodynamic, and kinetic models were used to explain the adsorption mechanism between Bromophenol blue, phenol, and GD particles. Thus, it was determined that the adsorption process between GD particles and Bromophenol blue was chemisorption, and between phenol and GD particles, physical adsorption took place. It was determined that GD particles polymer particles had high adsorption capacities, such as 136.40 mg/g for bromophenol blue and 98.26 mg/g for phenol than natural adsorbents. As a result, it was produced economical, simple, feasible, and functional adsorbents against anionic pollutants.
Keywords: Chromatography; Phenol; Organic Chemistry; Adsorption of Water Contaminants; Organic chemistry; Catalytic Reduction of Nitro Compounds; Analytical Chemistry; Chemistry; Chemical engineering; Engineering; Bromophenol blue; FOS: Chemical sciences; Environmental Science; Physical Sciences; Adsorption; Polymer; FOS: Chemical engineering; Water Science and Technology; Analytical Chemistry Techniques; Green Analytical Chemistry; 6. Clean water; 3. Good health; 13. Climate action